Review of the ‘Precarpathian University Bulletin. Philology’ (Issues 23– 35) - Dzhochka, Iryna (Journal of Vasyl Stefanyk Precarpathian National University, 2014)
The review focuses on the issues addressed by the contributors to the long-standing philological journal from the ‘Precarpathian University Bulletin’ series. The themes and contents of the articles in the fields of linguistics, literary criticism and folklore studies are highlighted; the major areas of research are characterized